1985
DOI: 10.1042/bj2260437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deuterium substitution α and β to the reaction centre, 18O substitution in the leaving group, and aglycone acidity on hydrolyses of aryl glucosides and glucosyl pyridinium ions by yeast α-glucosidase. A probable failure of the antiperiplanar-lone-pair hypothesis in glycosidase catalysis

Abstract: Neither kcat. nor kcat./Km for five aryl alpha-D-glucopyranosides correlates with aglycone pKa, and isotope effects, described according to the convention used by Cleland [(1982) CRC Crit. Rev. Biochem. 13, 385-428], of 18(V) = 1.002 +/- 0.008, alpha D(V) = 1.01 +/- 0.04 and alpha D(V/K) = 0.969 +/- 0.035 are observed for p-nitrophenyl, and one of beta D(V) = 1.02 +/- 0.04 for phenyl alpha-D-glucopyranoside; kcat. but not kcat./Km, correlates with aglycone pKa for five alpha-D-glucopyranosyl pyridinium ions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 39 publications
8
35
0
Order By: Relevance
“…Even deglycosylations or transglycosylations of glycosyl-enzyme intermediates appear to proceed in this way, and not through a reverse-type itinerary of the preceding glycosylation step. Arguments are given against the possible occurrence of a boat TS within a SLPH-compliant itinerary, whereas the alternative ALPHpathway ( Figure 7) can be supported by experimental evidence when revisiting results from a study 52 on kinetic isotope effects observed with enzymatic hydrolyses of aryl α-D-glucosides ( Figure 6). The route demarcations suggest a general mechanistic strategy for protection of the glycosyl-enzyme intermediate by transglycosidases: these may lock their intermediate in a nonproductive conformation for as long as the aglycon subsites are still occupied by water molecules solely, but once these are properly replaced by the carbohydrate-nucleophile, a minor amino acid residue reorientation (induced fit) may favor the productive pre-TS conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Even deglycosylations or transglycosylations of glycosyl-enzyme intermediates appear to proceed in this way, and not through a reverse-type itinerary of the preceding glycosylation step. Arguments are given against the possible occurrence of a boat TS within a SLPH-compliant itinerary, whereas the alternative ALPHpathway ( Figure 7) can be supported by experimental evidence when revisiting results from a study 52 on kinetic isotope effects observed with enzymatic hydrolyses of aryl α-D-glucosides ( Figure 6). The route demarcations suggest a general mechanistic strategy for protection of the glycosyl-enzyme intermediate by transglycosidases: these may lock their intermediate in a nonproductive conformation for as long as the aglycon subsites are still occupied by water molecules solely, but once these are properly replaced by the carbohydrate-nucleophile, a minor amino acid residue reorientation (induced fit) may favor the productive pre-TS conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent active-site-directed inactivation of yeast o-glucosidase by 1-fluoro-D-glucopyranosyl fluoride (6.19 mM) in 50 mM-sodium phosphate buffer, pH 6.8, at 25°C Logarithms of percentage residual activity are plotted against time: the lines are the least-squares best fits. The A symbols refer to the inactivation in the absence of a protecting agent, the El symbols to inactivation in the presence of 38.5 ,uM-l-deoxynojirimycin (K, 23/uM;Hosie & Sinnott, 1985). If the inactivation is assumed to be active-site-directed, these data give an apparent binding constant for the difluoride of 14 mm, compared with the K, for hydrolysis of 17.6 mM.…”
Section: Hydrolyses By Retaining Glucosidasesmentioning
confidence: 98%
“…This hyperconjugative weakening ofthe C-H or C-3H bond is at a maximum when the dehedral angle between the bond and the electrondeficient p orbital on the adjacent carbon atom is 00 and zero when it is 90°.} Thus for yeast a-glucosidase the value of AAGC is slightly higher than that for the spontaneous hydrolysis (18. kJ -mol-'), yet (V/K) for both aryl glucosides and a-glucosylpyridinium ions, and hence probably a-glucosyl fluoride, is governed by a non-covalent event, possibly a conjoint change of enzyme and substrate that puts the sugar ring in the 2" B conformation (Hosie & Sinnott, 1985). The value of AAGt, high though it is, is thus probably a lower limit.…”
Section: Hydrolyses By Retaining Glucosidasesmentioning
confidence: 98%
See 1 more Smart Citation
“…[15] The 2,5 B conformation has also been suggested by Hosie and Sinnott for the enzymatic hydrolysis of glucosides. [16] As part of an ongoing program on the implication of boat conformations in glycosyl transfer, [17] and regarding the importance of the 2,5 B conformation in enzymatic xyloside hydrolysis, we were interested in evaluating the anomeric reactivity of xylopyranosides when moving from the classic 4 C 1 conformation to the invoked 2,5 B conformation, which may stereoelectronically assist the formation and breakdown of the glycosidic bond. The influence of a boat conformation on the reactivity of simple tetrahydropyranyl acetals was previously investigated by Kirby, Deslongchamps and coworkers, [18] who studied acetals of type B in which the THP ring was fixed in the symmetrical boat conformation by a three-carbon bridge.…”
Section: Introductionmentioning
confidence: 99%